Silvopastoral systems as a strategy for drought resilience: A short international review - Mohammad Reza Ghaffariyan (Silva Balcanica)
Agroforestry is the combination of wooden plants (trees and shrubs) with agriculture or pasture from the same area. Silvopastoral systems combine natural resources such as planted trees and livestock in the land management unit. This combination would provide environmental and financial benefits. Some of the environmental benefits include aesthetics, water quality, improvement, soil conservation, carbon sequestration, biodiversity and fuel reduction. Using online search about 20 relevant research reports were found and reviewed to present the main research outcomes and experiences on silvopastoral systems around the globe. The results indicated that silvopastoral systems could be beneficial to the landowners and farmers which could improve drought resilience by increasing air humidity and reducing weather temperature impact which eventually contributed to mitigation fire risks in farms. From a financial perspective, silvopastoral systems proved to be an attractive financial practice especially when silvicultural treatments were implemented in year zero to increase timber production. The negative aspects were long payback periods and high risk to consider in native forest management.